On the Promise of Piety - Adeed, Farah (Universitas Islam Internasional Indonesia (UIII), 2024)
Khan, A. (2024). The Promise of Piety: Islam and the Politics of Moral Order in Pakistan. Cornell University Press. In an era when the dominant normative view is to confine religion to the private sphere, and when public displays of religious devotion are often perceived as an overabundance of emotion, indicating an absence of rational thought and potentially undermining social stability, an anthropologist's nuanced exploration of Islamic piety deserves social scientists’ careful attention.